Turkey in the Cold War ideology and culture - Örnek, Cangül 1978-; Üngör, Çagdas 1976- (Palgrave Macmillan, 2013)
"Turkey in the Cold War: Ideology and Culture examines Turkey's Cold War experiences from a social and cultural perspective. Analyzing the local impact of this global confrontation in Turkey, this volume complicates the picture portrayed in the conventional studies on the Cold War era, most of which focused on the country's role in the US-led Western alliance. This volume, by contrast, shifts the focus to the contested Cold War culture in Turkey and examines several of its neglected themes, such as international exhibitions, sport activities and literature, media and propaganda, as well as the reception of US aid and assistance"-- c Provided by publisher